2021
DOI: 10.3390/ijerph18020636
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Depression in Portuguese Healthcare Workers during the COVID-19 Pandemic—The Mediating Role of Psychological Resilience

Abstract: During the COVID-19 pandemic, healthcare workers (HCW) have been exposed to multiple psychosocial stressors. Resilience might protect employees from the negative consequences of chronic stress. The aim of this study was to explore the mediating role of resilience in the relationship between depression and burnout (personal, work-related, and client-related). A cross-sectional study was performed using an online questionnaire distributed via social networks. A survey was conducted comprising standardized measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
108
1
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(136 citation statements)
references
References 44 publications
15
108
1
12
Order By: Relevance
“…A large number of factors interact in various ways in the workplace; among other things, all pre-existing inequalities can be accentuated during the pandemic, for example, gender inequities can be enhanced in times of pandemic [26]. In the fight against COVID-19, BOS has been described as a major threat to the stability of the frontline workforce [27][28][29][30]. The confrontation with a new, highly diffusive disease exposes workers to significant stress that can affect mental health in different ways; acute stress will mainly cause anxiety, mood changes, sleep disorders, fear, and post-traumatic stress disorder, while chronic stress may cause BOS, which is a condition strongly linked to impaired work ability [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of factors interact in various ways in the workplace; among other things, all pre-existing inequalities can be accentuated during the pandemic, for example, gender inequities can be enhanced in times of pandemic [26]. In the fight against COVID-19, BOS has been described as a major threat to the stability of the frontline workforce [27][28][29][30]. The confrontation with a new, highly diffusive disease exposes workers to significant stress that can affect mental health in different ways; acute stress will mainly cause anxiety, mood changes, sleep disorders, fear, and post-traumatic stress disorder, while chronic stress may cause BOS, which is a condition strongly linked to impaired work ability [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Resilience might protect ICU workers from burnout, as reported in a Canadian qualitative study [ 18 ]. Resilience is described as the ability to face problems and adapt to adverse conditions [ 19 , 20 ]. Two recent studies explored the relation between resilience and burnout among healthcare workers during the COVID-19 pandemic: they revealed that psychological resilience could have a mediating role between mental health outcomes and all burnout dimensions [ 17 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Positive psychological changes and post-traumatic growth, associated with psychological resilience, have also been reported when the COVID-19 pandemic was compared to Hurricane Katrina [ 21 ]. Psychological resilience [ 22 , 23 ]—understood as the ability to positively adapt to situations that can potentially cause stress and anxiety, such as COVID-19—and satisfaction with life can present themselves as protective variables.…”
Section: Introductionmentioning
confidence: 99%